PENGARUH SINAR ULTRAVIOLET DAN LAPISAN BAHAN SILICON RUBBER PADA ISOLATOR POLYETHYLENE TERHADAP SUDUT KONTAK DAN ARUS BOCOR DALAM KONDISI KERING DAN BASAH - Sabila Azmil Khaqqi; Moch. Dhofir; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
This study describes the effect of variations in ultraviolet light, the silicon rubber coating on the insulator on the level of leakage current and the contact angle, in this study the insulator is made of polyethylene with two variations of angles, namely angles of 120° and 150° where there are two insulators with different conditions, namely coating and no lining. The research method used is to take data on leakage current and contact angle directly at the High Voltage Engineering Laboratory, University of Brawijaya, the test is carried out using AC voltage with a variation of the test voltage of 2 kV, 4 kV, 5 kV, 6 kV, 8 kV, 10 kV , 12 kV, 14 kV, 15 kV, 20 kV and 25 kV. Tests were carried out using 2 conditions for each insulator, namely before and after ultraviolet light irradiation with variations of 12 and 14 hours which were then tested in dry conditions and wet conditions with variations in wetting discharge 10, 30, and 60 mL/s which refers to Rainfall trend in Indonesia. Testing the contact angle on the insulator using irradiation variations of 0, 2, 4, 6, 8, 10, 12, and 14 hours. The results obtained in this study include knowing the level of leakage current in each insulator, especially comparing dry conditions and the presence of wet conditions with an increase in wetting discharge so that the surface resistance is known and also the power loss caused by the insulator. The results obtained from this study include the addition of coating causing an increase in the contact angle and the size of the leak and the greater the addition of the fin angle will cause an increase in the leakage current level, besides that the wetting current discharge also affects the leakage current, where the increase in the insulator leakage current level is directly proportional with the addition of wetting discharge. Keywords — Polyethylene insulator, Angle contact, leakage current, ultraviolet, silicone rubber, dry and wet condition